1999
DOI: 10.1007/s003450050106
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic interstitial cryotherapy of the adrenal as a treatment modality

Abstract: Adrenalectomy is indicated for patients with large adrenal lesions or functional tumors. Cryoablation is currently used as a surgical alternative for the treatment of prostate, lung, brain, pharynx, and liver tumors. The purpose of this study was to determine if cryosurgery could be delivered to small areas in the adrenal gland in a controllable and reproducible manner such that tissue could heal in a nonpathologic way. A total of 14 female mongrel dogs underwent acute (n = 8) or chronic (4 weeks, n = 6) cryoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…7,[11][12][13][14] Thermal ablation of tumors including cryosurgery, microwave ablation, and radiofrequency ablation (RFA) have developed rapidly in human surgery. 7,11,[15][16][17] Most tumor ablation devices currently used clinically in humans use radiofrequency current, which generate frictional heating from ion agitation, i.e. the same process used in electrocautery.…”
Section: Introductionmentioning
confidence: 99%
“…7,[11][12][13][14] Thermal ablation of tumors including cryosurgery, microwave ablation, and radiofrequency ablation (RFA) have developed rapidly in human surgery. 7,11,[15][16][17] Most tumor ablation devices currently used clinically in humans use radiofrequency current, which generate frictional heating from ion agitation, i.e. the same process used in electrocautery.…”
Section: Introductionmentioning
confidence: 99%
“…In our experience, with the patient in the 60° flank position, correct identification of the left renal and adrenal vein is always feasible – even in patients with considerable fibro–fatty retroperitoneum; consequently, we do not believe that a laparoscopic ultrasound probe is necessary during adrenal surgery. Schulsinger et al [33]recently reported their experience when using a cryotherapy probe in the canine model to perform partial adrenal ablation – which, in some cases, may be recommended. Moreover, Janetschek et al [21]and Imai et al [34]reported the feasibility of successful partial adrenalectomy with, in humans, excellent preservation of the adrenal function.…”
Section: Discussionmentioning
confidence: 99%
“…Mais recentemente, novas técnicas foram apresentadas, como adrenalectomia por minilaparoscopia (instrumentos menores de 3mm), adrenalectomia robótica com telepresença, crioablação adrenal intersticial, ablação de tumores por radiofreqüência, injeção de ácido acético por via percutânea guiada por TC 15,223,[228][229][230][231][232][233][234][235] .…”
Section: Procedimentos Cirúrgicosunclassified